THEORETICAL AND METHODOLOGICAL BASIS OF NATIONAL ECONOMY SUSTAINABILITY AND HUMAN DEVELOPMENT IN UKRAINE - Саричев, В.І.; Копаничук, К.О. (SWorldJournal, 2025)
The purpose of the article is to study the theoretical and methodological principles of ensuring the sustainability of the national economy and human development in Ukraine in the context of deep socio-economic transformations and external challenges caus